Expression of voltage-gated K+ channels in insulin-producing cells. Analysis by polymerase chain reaction. - Betsholtz, C; Baumann, A; Kenna, S; Ashcroft, F; Ashcroft, S; Berggren, P; Grupe, A; Pongs, O; Rorsman, P; Sandblom, J (1990)
We have used the polymerase chain reaction (PCR) with primers against the S5 and S6 regions of voltage-gated K+ channels to identify 8 different specific amplification products using poly(A)+ RNA isolated from islets of Langerhans from obese hyperglycemic (ob/ob) mice and from the two insulin-producing cell lines HIT T15 and RINm5F. Sequence analysis suggests that they derive from mRNAs coding for a family of voltage-gated K+ channels; 5 of these have been recently identified in mammalian brain and 3 are novel. These hybridize in classes to different mRNAs which distribute differently to a number of tissues and cell lines including insulin-producing cells.